Análise da relevância clínica da classificação histológica dos carcinomas de mama de tipos lobular e ductal e sua relação com a classificação molecular - Moraes Neto, Francisco Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
INTRODUCTION: The prognostic value of the molecular classification of breast cancer recently proposed has been validated by many studies. However, the great majority of these studies has focused on invasive ductal carcinoma no special type (IDC), a widely recognized heterogeneous entity. Few papers have studied other special types of breast cancer such as invasive lobular carcinoma (ILC) the most common special type. ILC shows clinico-pathological features and natural history quite distinctive from IDC being clearly separate biologic entities. Moreover, ILC is relatively frequent and has been increasing in incidence over the recent years. OBJECTIVE: to study comparatively the luminal molecular subtypes A e B of two groups of patients with ILC and IDC and to determine the prognostic independent value of the molecular classification in ILC patients by correlating the molecular subtypes with clinical outcomes such as breast cancer specific survival (BCSS) and overall survival (OS). MATERIALS AND METHODS: archival paraffin blocks from women diagnosed with ILC and IDC at the Pathology Laboratory of Hospital Amaral Carvalho, Jau, Sao Paulo, Brazil, were retrieved. Patient's charts and the Hospital Amaral Carvalho Cancer Registry were consulted for obtaining the staging and follow-up information (median 121.77 and 131.27 months for ILC and IDC, respectively) and 186 patients were selected. Two samples from each paraffin block were extracted to mount tissue microarray (TMA) blocks by using a Tissue Microarray Builder ab1802 (Abcam®, Cambridge, UK). The following immunohistochemical markers were performed in the TMA blocks: estrogen receptor α, progesterone receptor, HER2 and Ki67 protein. The intrinsic molecular subtypes (luminal A, luminal B, HER2 and triple negative) were determined based on the immunohistochemical profile of each tumor. Prognostic clinico-pathological features were analysed in absolute (n) and relative frequency (%). The ...

INTRODUÇÃO: O valor prognóstico da classificação molecular do carcinoma de mama recentemente proposta tem sido validado por numerosos estudos. Entretanto, a maioria destes trabalhos estudou o tipo histológico mais comum denominado carcinoma ductal invasivo usual (CDI), uma entidade reconhecidamente heterogênea. Poucos estudos concentraram-se especificamente em outros tipos histológicos como o carcinoma lobular invasivo (CLI) que é o tipo especial mais frequente. O CLI apresenta-se com características clínico-patológicas e história natural bastante distintas do CDI sendo claramente entidades biológicas diferentes. Além disso, é uma doença relativamente frequente com aumento de sua incidência no mundo. OBJETIVO: Estudar comparativamente os subtipos moleculares luminais A e B de dois grupos de pacientes com CLI e CDI da mama, bem como determinar o valor prognóstico independente da classificação molecular nestes tumores correlacionando os subtipos moleculares com a sobrevida específica por carcinoma de mama (BCSS) e a sobrevida global (OS). SUJEITOS E MÉTODOS: Estudo do tipo transversal analítico. Foram selecionados blocos de parafina de mulheres com diagnóstico histopatológico de CLI e CDI no Laboratório de Patologia do Hospital Amaral Carvalho (HAC), Jaú, São Paulo, Brasil. Os respectivos prontuários médicos e o Registro Hospital de Câncer (RHC) do HAC foram consultados para a pesquisa das informações clínicas e de seguimento destas mulheres (média de 121,77 e 131,27 meses para o CLI e CDI, respectivamente), totalizando 186 casos. Dos blocos doadores, foram extraídas duas amostras de 2 mm de diâmetro e depositadas nos blocos de parafina receptores usando Tissue Microarray Builder ab1802 (Abcam®, Cambridge, UK). Nestes cortes foi feita a pesquisa dos seguintes marcadores imunoistoquímicos: receptor de estrógeno α (RE), receptor de progesterona (RP), HER2 e Ki67. Os subtipos moleculares (luminal A, luminal ...
Keywords: Mamas - Cancer; Carcinoma ductal de mama; Carcinoma lobular; Estudos transversais; Tumores; Carcinoma, Ductal, Breast; Carcinoma, Lobular